DESIGN OF A LIFTER FOR HORIZONTAL CHAMBER MACHINE IN A LEAF SPRING PRODUCTION LINE: A CASE STUDY AT PT. XYZ - Ahmad Saepuddin; Rachman Arya Syahputra (Universitas Negeri Surabaya, 2026)
PT. XYZ is an automotive manufacturing company that produces leaf springs. One of the machines used in the leaf spring forming process is a Horizontal Chamber Machine that works by pressing. In its operation, this machine requires a lifter to assist in the transfer of leaf springs and reduce the risk of workplace accidents. The lifter has a frame component that functions as the main structure in supporting the load during the lifting and lowering of the leaf spring. Therefore, it is necessary to design a lifter frame that is safe and capable of withstanding the working load that occurs during the production process. This study aims to design and evaluate the strength of the lifter frame to ensure its safety in operational use. There are three variations of frame designs differentiated by material thickness, namely 10 mm, 12 mm, and 14 mm. The simulation results show that the maximum stress in frame design 1 is 24 MPa, frame design 2 is 16 MPa, and frame design 3 is 12 MPa. The strain values for each design are 0.000066, 0.000048, and 0.000036, while the displacement maximum values are 0.026 mm, 0.016 mm, and 0.016 mm. The safety factors obtained are 11, 15, and 19, respectively. The fatigue life value for all frame designs is cycles. Based on these simulation results, frame design 1 is declared to have met the strength and safety criteria required for use in the production process